- #1

- 1,026

- 0

**[SOLVED] Rearranging a Relativity Equation**

## Homework Statement

Rewrite equation:

[tex] f = \sqrt{\frac{c + u}{c - u}}f_0 [/tex]

to find the relative velocity

*u*between the electromagnetic source and an observer in terms of the ratio of the observed frequency and the source frequency of light.

What relative velocity will produce a 3.0 decrease in frequency and

## Homework Equations

Rearangement of:

[tex] f = \sqrt{\frac{c + u}{c - u}}f_0 [/tex]

## The Attempt at a Solution

I seem to get stuck when trying to rearrange the equation:

[tex] f = \sqrt{\frac{c + u}{c - u}}f_0 [/tex]

[tex] \frac{f}{f_0} = \sqrt{\frac{c + u}{c - u}} [/tex]

[tex] (\frac{f}{f_0})^2 = \frac{c + u}{c - u} [/tex]

[tex] (c - u)(\frac{f}{f_0})^2 = c + u [/tex]

But I am not sure where to go from here.

Any suggestions?

TFM